School Economics in the National Repository of Open Educational Resources (NROER) An overview of the developmental process - Khan, Aerum (JOURNAL OF INDIAN EDUCATION, 2014)
Open Educational Resources (OERs) are increasingly being promoted by enthusiasts in the field of education as a solution to the challenges of access, quality and cost of digital content worldwide. The National Policy on Information and Communication Technology by Ministry of Human Resource Development, Government of India (2012), in its policy goals discusses about creating an environment for collaboration, cooperation, sharing and promoting universal, equitable, open and free access to ICT. The most important aspect of openness is the free availability of resource over the Internet, and recurrence of as few as possible restrictions, in the form of licensing activity, on the use of resource by the users. Central Institute of Educational Technology (CIET), National Council of Educational Research and Training (NCERT) and Department of School Education and Literacy, Ministry of Human Resource Development, Government of India has launched National Repository of Open Educational Resources (NROER), which is a digital repository of open educational resources offering resources for all school subjects and grades in multiple languages. The resources are available in the form of concept maps, videos, multimedia, interactive objects, audio clips, talking books, photographs, diagrams and charts, articles, lesson plans and textbook pages. This research paper provides a glimpse to the NROER with special reference to the Economics content of Secondary school level. It is an attempt to provide an overview to the complete methodology of development of Economics content in the form of concepts, concept maps and multiple resources on the NROER.